Daily, self-test rapid antigen test to assess SARS-CoV-2 viability in de-isolation of patients with COVID-19 - Bae, Seongman; Park, Heedo; Kim, Ji Yeun; Park, Sunghee; Lim, So Yun; Bae, Joon-Yong; Kim, Jeonghun; Jung, Jiwon; Kim, Min Jae; Chong, Yong Pil; Lee, Sang-Oh; Choi, Sang-Ho; et al. (Frontiers in Medicine, 2022)
Background Isolation of COVID-19 patients is a crucial infection control measure to prevent further SARS-CoV-2 transmission, but determining an appropriate timing to end the COVID-19 isolation is a challenging. We evaluated the performance of the self-test rapid antigen test (RAT) as a potential proxy to terminate the isolation of COVID-19 patients. Materials and methods Symptomatic COVID-19 patients were enrolled who were admitted to a regional community treatment center (CTC) in Seoul (South Korea). Self-test RAT and the collection of saliva samples were performed by the patients, on a daily basis, until patient discharge. Cell culture and subgenomic RNA detection were performed on saliva samples. Results A total of 138 pairs of saliva samples and corresponding RAT results were collected from 34 COVID-19 patients. Positivity of RAT and cell culture was 27% (37/138) and 12% (16/138), respectively. Of the 16 culture-positive saliva samples, seven (43.8%) corresponding RAT results were positive. Using cell culture as the reference standard, the overall percent agreement, percent positive agreement, and percent negative agreement of RAT were 71% (95% CI, 63–78), 26% (95% CI, 12–42), and 82% (95% CI, 76–87), respectively. The sensitivity, specificity, positive predictive value, and negative predictive value of the RAT for predicting culture results were 44% (95% CI, 20–70), 75% (95% CI, 66–82), 18% (95% CI, 8–34), and 91% (95% CI, 84–96), respectively. Conclusion About half of the patients who were SARS-CoV-2 positive based upon cell culture results gave negative RAT results. However, the remaining positive culture cases were detected by RAT, and RAT showed relatively high negative predictive value for viable viral shedding.